(untitled) (Journal of Human Sciences, 2021)
This study dealt with an important topic that talks about an Imam and the author of the doctrine of Imam Ibn Hazm. The research, in this research, deals with the problematic situation that surrounds the opinion of Ibn Hazm in the doctrinal issues and the offensive views against a famous Imam such as Kal-Baqlani, and a doctrinal school of the size of the Ash’ari school. This study aims at translating Imam Ibn Hazm, and then identify his position on the Ash’ari school. It also aims to explain his dereliction of this ancient school>. It is the speaking tongue of the doctrine of the Sunnah and the group. The study shows the correct face and the most precise opinion when comparing Ibn Hazm with the views of Imam Al-Baqlani. This study, in particular, discusses the fact that Ibn Hazm quoted texts from al-Baqlani, and the analytical method used, and relied on the method of comparison between what Ibn Hazm aimed to and what is proven in the books of Imam al-Baqlani, and also the difference between what Ibn Hazm transmitted and what is found in the books of Imam Al-Baqlani himself. The study concluded that many of the issues that the Ash’aris discussed were not understood by their opponents, which often led to confusion and accusing them inappropriately, as they were innocent.